PENGAWASAN CAMAT DALAM PENATAAN PEMUKIMAN KUMUH DI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Rahmi, Fitria; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Growth and development of an area of town is not always a positive affect. High population growth resulted in increased population density and an increased in the density of buildings for residential as well as an increased need of infrastructure to carry out activities in an effort to make ends meet. The increase in space requirements is almost always coupled with the growth and development of slums and squatter settlements in a region.Tassel coastal districts is one district that has slums, the residential area is located in one of the villages Meranti Pandak subdistrict coastal fringe. Villages that cannot escape the problem of untidiness. If it is left without treatment improvements will expand the existing slums. Efforts taken by the government to address this is through the implementation of the restructuring program of slums that have been implemented since the first approach taken by various coastal fringe districts, including mutual cooperation program of activities that include physical, environmental, and infrastructure there.One of the government programs in addressing the slum is a slum arrange evenly and thorough quality improvement in a very seedy area.This study aims to determine how much oversight arrangement slum districts on the fringe of society in the coastal city of Pekanbaru. The method used to achieve the purpose of the research is qualitative method.Keywords : Seedy, Structuring, Regulation, Supervision, Slums.